Effect of Alcohol on the Proestrous Surge of Luteinizing Hormone (LH) and the Activation of LH-Releasing Hormone (LHRH) Neurons in the Female Rat - Ogilvie, Kathleen M. (J Neurosci, 1997)
Reproduction is adversely affected by alcohol abuse in humans and laboratory animals. In rats, alcohol exposure suppresses both luteinizing hormone (LH) and sex steroid secretion, although consensus is lacking as to which level of the hypothalamic-pituitary-gonadal (HPG) axis is primarily affected. We tested the hypothesis that acute alcohol treatment inhibits the HPG axis by blunting release of LH-releasing hormone (LHRH) in female rats, by examining the effect of this drug on the central reproductive endocrine event; i.e., the proestrous surge of gonadotropins, which triggers ovulation. In a first series of experiments, we injected alcohol at 8 A.M. and 12 P.M. on proestrus and measured plasma levels of LH, estradiol (E(2)), and progesterone during the afternoons of proestrus and estrus. Alcohol administration blocked the proestrous surge of LH and ovulation. In subsequent experiments, alcohol inhibited the surge of LHRH (measured by push–pull cannulation) and LHRH neuronal activation (measured by Fos labeling in LHRH neurons). Because alcohol also decreased E(2) levels, we reasoned that it might have prevented positive feedback; however, alcohol retained its ability to inhibit the LH surge evoked by E(2) implantation in ovariectomized females, disproving this hypothesis. Additionally, alcohol does not act via increased corticosteroid secretion, because alcohol also blocked the proestrous surge in adrenalectomized females. Last, exogenous administration of LHRH to alcohol-blocked animals evoked LH secretion and ovulation, indicating that pituitary and/or ovarian function could be restored by mimicking the hypothalamic signal. Collectively, these data indicate that in female rats, alcohol inhibits the gonadotropin surge primarily by decreasing LHRH secretion.